¿Cómo estudiar el racismo en la prensa escrita deportiva? - Gonzales, Sharún (2018)
Ethnic and racial stereotypes are part of the language that the Peruvian sports press uses in the construction of news. At the same time, such press replicates the complaints of racist events in football.This article refl ects on a methodological strategy to examine the coexistence of both elements in the Peruvian sports press. Taking into account the specific characteristics of this type of press and the particularity of racism in Peru, we detect the need to use a research approach that addresses diff erent dimensions of both textual discourse and discourse as a social, cultural and discursive practice.It is a process that relates three stages of data collection: content analysis, critical discourse analysis and in-depth interviews with discourse producers. Put in dialogue, the results of the three analyzes show that the apparently contradictory relationship between the discourse and the practice of the Peruvian sports press are in fact coherent with the naturalization of racism in Peruvian society.